The hematological impact of umbilical cord milking versus delayed cord clamping in premature neonates: a randomized controlled trial - Hytham Atia; Ahmed Badawie; Osama Elsaid; Mahmoud Kashef; Nourhan Alhaddad; Mohamed Gomaa (BMC Pregnancy and Childbirth)
Abstract Background The hematological impact of umbilical cord milking (UCM) was compared to that of delayed cord clamping (DCC) as a faster placental transfusion technique for preterm neonates (between 24 and 34 + 6 weeks gestation). A comparison of important neonatal morbidities was also made. Methods This was an open-label randomized trial conducted from June 8, 2017, to April 22, 2019. Two hundred patients with preterm deliveries (24 and 34 + 6 weeks gestation) were assigned to the DCC or UCM group at random at a ratio of 1:1. The study power was 80% for a difference in the hematocrit value of 3% and Hb value of one gram, and an alpha error of 0.05. Results The following variables were analyzed in the comparison of UCM vs. DCC: first draw hemoglobin: 17.0 ± 1.9 vs. 16.8 ± 1.8 gm/dl (95% CI -0.75–0.29, P 0.383); first draw hematocrit: 55.6 ± 6.4 vs. 55.2 ± 6.4% (95% CI -2.18–1.38, P 0.659); peak hematocrit: 56.9 ± 6.4 vs. 56.3 ± 6.7% (95% CI -2.41–1.26, P 0.537); the need for respiratory assistance (47% vs. 30%, P 0.020), inotropes (16% vs. 6%, P 0.040), and blood transfusion (26% vs. 12%, P 0.018); and the occurrence of intraventricular hemorrhage (9% vs. 5%, P 0.407), necrotizing enterocolitis (6% vs. 2%, P 0.279), sepsis (25% vs. 15%, P 0.111), and neonatal death (13% vs. 4%, P 0.40). Conclusion UCM facilitated a rapid transfer of placental blood equivalent to that of DCC for premature neonates. However, it resulted in increased rates of interventions and morbidities, especially in extremely preterm neonates. Trial registration The clinical trial was registered on May 10, 2017, with registration number (NCT03147846).